The importance of modern information technology for making business decisions - Nikolić Miloš; Vesić Tamara; Gavrilović Milan (Trendovi u Poslovanju)
The first part of this paper discusses the rapid development of information technologies that have helped market globalization, competition, connectivity, faster flow of information, the creation of brand new products, which has led to a change in everyday life in which managers have to make different strategic, tactical and operational decisions. Also, the term management of information system is explained as an integral part of the process of planning, organizing and controlling the work in the conditions of the decision-making process, as a creative finalization of the management process. The special part deals with the organization and planning of information system management. It should be borne in mind that information, as a set of data, is always related to some system and processes, which implies that it can be any kind of system, from a technical device, through an organizational system, to a biological system. Therefore, the automation of information processing, as an IT object, is a general term and applies to all areas of human activity. In the final part we are talking about determining the price of information system management as a product and forecasting the budget for this function.